Copying a Plasmonic Signal From an Optical Signal - Sung-Ryoung Koo; Guhwan Kim; Dong Hun Lee; Kyung-Jo Kim; Myung-Hyun Lee (IEEE Photonics Journal, 2020)
We propose a plasmonic signal copier (PSC) composed of a gapped surface plasmon polariton waveguide (SPPW) and an optical waveguide laid across the gap. The interaction between an SPP and an optical signal around the gap edge is demonstrated experimentally and numerically with polarizations of the incident optical wave. A plasmonic signal is invertedly copied from a TE-polarized optical signal incident to the optical waveguide. The symmetrically distributed charges induced from the TE-polarized optical waves on the metal gap edges of input/output SPPWs were determined to be an essential trigger of the copied plasmonic signal. The characteristics of the PSC enable creation of a plasmonic-based circuit system that is compatible with an optical-based circuit system.